Instrumento para avaliação da formação em saúde segundo as diretrizes curriculares nacionais - Nogueira, Rafaela Raulino (2019)
Introduction: It is possible to see the change in the process of training of health professionals over the years: the disease-centered vision turned to a holistic view of the subject; a model of purely assistentialist character became a model that sees the importance of prevention and promotion to health; care directed only by a professional is focused on interprofessional health work. One of the actors who promoted this reorientation of the training was the establishment of the National Curriculum Guidelines (DCN) that serve as a basis for the construction of the pedagogical projects of courses (PPC). Objective: To Adapt and validate a tool based on the National curriculum guidelines for evaluation of the training courses of the health area. Materials and methods: this is a cutting from a major project entitled "assessment of healthcare Courses at the Federal University of Paraíba: perspectives of teachers and students in different methodological approaches ", descriptive and exploratory and quantitative and qualitative nature. The original instrument consisted of 4 dimensions and 20 sub-dimensions – profile of the future graduates (Q1 to Q5), guidance on health Care – (Q6), teaching-Service integration (Q11 and Q12) and pedagogical approach (Q13 to Q20). The validation of the instrument included two validation processes after its initial adaptation: Content validation (through the analysis of 08 specialists who met the criteria established in the research) and statistical validation (through the use of confirmatory factor analysis-AFC) performed after the conduction of the exploratory factor analysis (AFE). Results and discussion: All dimensions and their compositions (subdimensions) reached averages and standard deviations within the established by the research and the suggestions for textual reformulation were consolidated and altered when necessary. The questionnaire after content validation was applied to 302 students from the last periods of health courses of a federal public university. With the structured database, AFE provided the best results with the removal of questions Q3 (Autonomous) and Q20 (Teaching-Research-Extension Articulation), remaining 18 questions, besides achieving good results regarding the Kaiser- Meyer- Olkin (KMO), Bartlett's Sphericity Test (BTS) and Sample Suitability Measure (MAA), determining the retention of 3 dimensions representing a total of 60.67% of the total variability of the variables. Cronbach's alpha result (α = 0.921) indicated internal consistency of the instrument, favoring the onset of AFC. The results of the AFC were satisfactory regarding the measurement model (presenting Convergent Validity and Discriminant Validity of the three factors / sub-dimensions), as well as the structural model (evaluated through the model adjustment indices). Conclusion: The DCN Health Training Assessment Instrument became valid and reliable, as it met all the validation process requirements used in this study, allowing its use in academia. The application of the same may provide health courses with self-assessment, aiming at the adequacy and possible pedagogical and/or curricular changes that may favor the health training process according to the profile of egress proposed in the DCN.